DEVELOPMENT OF WAREHOUSE ROBOT WITH ADVANCED LINE FOLLOWING AND BACKGROUND COLOR SENSORS - Lok, J.W.; Muda, W.M.W.; Woro, A.N. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
Warehouse robot uses normal line following sensor to move and deliver inventory around the warehouse. The main disadvantage of the sensor is its inaccuracy in sensing due to different lighting conditions. Therefore, an autonomous robot with advanced line following sensor that is capable of detecting any line color with different brightness and background color is developed. In addition, the color sensor is integrated into the robot to detect the background color to determine the speed of the robot. The objectives are achieved by investigating the characteristics of the sensors to establish the relationship between the input and output of both sensors, design circuit connection, develop the code for the robot using Arduino Uno controller, and test run the performance of the developed robot with output observation. Results show that, the robot with advanced line following sensor was able to move and follow correctly black line with different background colors, where the robot had changed its speed accordingly when enter different zones. Findings from the project can be used to increase performance of warehouse robot in industry at different zones with different conditions.